Global Dynamics of a Discretized Heroin Epidemic Model with Time Delay - Xamxinur Abdurahman; Ling Zhang; Zhidong Teng (Abstract and Applied Analysis)
We derive a discretized heroin epidemic model with delay by applying a nonstandard finite difference scheme. We obtain positivity of the solution and existence of the unique endemic equilibrium. We show that heroin-using free equilibrium is globally asymptotically stable when the basic reproduction number R0<1, and the heroin-using is permanent when the basic reproduction number R0>1.